"A Level Playing Field"? – What an Environmental Justice Lens Can Tell us about Who Gets Leveled in the Forest Law Enforcement, Governance and Trade Action Plan. Issue 7 (2nd July 2020) - Maryudi, Ahmad; Acheampong, Emmanuel; Rutt, Rebecca L.; Myers, Rodd; Dermott, Constance L.
Abstract: The European Union introduced Forest Law Enforcement, Governance and Trade (FLEGT) Action Plan, with Voluntary Partnership Agreements (VPA) and the EU Timber Regulation (EUTR) as the key components. The VPA and EUTR have been conceived as complementary tools to establish a "level playing field." This paper analyses how a level playing field has been conceptualized, approached, and experienced in practice. It focuses on the adoption and implementation of EUTR and VPA in Europe, Indonesia, and Ghana. Our research highlights inequities in the practice of "leveling" and outcomes from a presumed level field. Stakeholder engagement excluded some factions of the private sector, notably SME operators, favoring select NGOs in general. New systems also favor larger operators who possess more capacity to deal with legality requirements. This leads small operators to perceive of a so-called level playing field as one in which they are disadvantaged, indicating multiple injustices against already vulnerable groups.